Analysis of Consumer Market Preferences of Electronic Products In 8 Sub-Districts of South Bogor to Predict Demand In PT. Ruma - Vicianti Nindyantika (Social Economics and Ecology International Journal (SEEIJ), 2021)
Understanding the factors that influence preference is an opportunity for companies to understand market segments. With market segmentation, marketers can identify potential group and predict customer demand. Understanding the market segment can also make marketers develop strategies of differentiation and positioning formation on the right target market. This study aims to determine the market preference for electronic products based on psychographic segments to predict demand of member PT. RUMA. Methods of data collection using questionnaires distributed to 100 customers by using conjoint and cluster analysis.